Best of UNICEF Research 2015 - UNICEF Innocenti Research Centre (United Nations, 2015)
The Best of UNICEF Research, now in its third year, showcases and recognizes high-quality, high-impact research being done in the organization. The intention of the project is to communicate that UNICEF is often engaged in supporting a range of cutting-edge research to improve the lives of children. Yet this is often poorly known. The ‘Best of UNICEF Research’ initiative aims to change this perception. This publication presents summaries of twelve of the projects submitted to the 2015 Best of UNICEF Research competition which illustrate the range of research being undertaken. The 12 projects in the final selection cover many of the ‘traditional’ areas of UNICEF work (health, nutrition, sanitation and education), while also highlighting issues that have more recently gained prominence within the global policy agenda, such as social transfers, violence against children and school bullying, and various forms of inequality or exclusion